Analisis kinerja komite pada Tour de Borobudur ke-23: Pendekatan psikologis - Sugiyono, Indriani Novelia; Anggita, Gustiana Mega; Rahayu, Tandiyo; Ali, Mohammad Arif; Castyana, Billy (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
Psychological factors are one of the aspects that influence committee performance. The better the psychological quality of individuals, the higher the performance produced. This study aims to analyze the performance of the Tour de Borobudur XXIII committee through a psychological approach. The research method used is quantitative descriptive with an online questionnaire (Google Form) as the research instrument. With the purposive sampling technique, 29 research samples were obtained that met the inclusion and exclusion criteria. Data collection was conducted using a standardized questionnaire with a Likert scale, assisted by SPSS software. The questionnaire was used to analyze psychological indicators such as personal beliefs, task meaning, social pressure, career opportunities, interpersonal development, love events, extrinsic rewards, self-autonomy, psychological contracts, and job satisfaction as aspects of evaluating the performance of the Tour de Borobudur committee. The study's results indicate that the performance of the Tour de Borobudur XXIII committee falls into the moderate category. With a score of 3 out of 29 committee members falling into the very good category, 4 committee members in the good category, 12 committee members in the moderate category, 8 committee members in the poor category, and 2 committee members in the very poor category. The conclusion is that psychological factors influence the performance level of the Tour de Borobudur committee. Through psychological approach instruments, committee performance is expected to be analyzed and provide accurate information regarding individual committee performance. The study provides an overview of committee performance based on a psychological approach.